Anti- and pro-oxidative mechanisms comparing the macular carotenoids zeaxanthin and lutein with other dietary carotenoids – a singlet oxygen, free-radical in vitro and ex vivo study. Issue 8 (26th June 2020) - Boehm, Fritz; Edge, Ruth; Truscott, T. George
Abstract : The macular pigment lutein is shown to be a particularly efficient protector compared to other dietary carotenoids against a range of specific ROS at all oxygen concentrations. Abstract : The interactions of dietary carotenoids, and particularly the xanthophylls in the macula, with singlet oxygen and three different oxy-radicals, (hydroxyl radical, nitrogen dioxide and the superoxide radical anion) are compared using pulsed laser and γ-techniques. The results give possible molecular mechanisms for the switch from anti-oxidant (protection) by carotenoids to pro-oxidant (damage) by carotenoids. The participation of oxygen in radical mechanisms in the presence of different carotenoids is compared for the different radicals. It is shown that the mechanistic role of oxygen differs very significantly for anti-/pro-oxidation by hydroxyl radicals when compared to nitrogen dioxide. Lutein was found to be an extremely good cell protector against hydroxyl radicals at all oxygen concentrations, including under physiological conditions.